SiRNA Mediated Knockdown of Tissue Factor Expression in Pigs for Xenotransplantation. Issue 5 (23rd March 2015) - Ahrens, H. E.; Petersen, B.; Herrmann, D.; Lucas‐Hahn, A.; Hassel, P.; Ziegler, M.; Kues, W. A.; Baulain, U.; Baars, W.; Schwinzer, R.; Denner, J.; Rataj, D.; et al.
Abstract: Acute vascular rejection (AVR), in particular microvascular thrombosis, is an important barrier to successful pig‐to‐primate xenotransplantation. Here, we report the generation of pigs with decreased tissue factor (TF) levels induced by small interfering (si)RNA‐mediated gene silencing. Porcine fibroblasts were transfected with TF‐targeting small hairpin (sh)RNA and used for somatic cell nuclear transfer. Offspring were analyzed for siRNA, TF mRNA and TF protein level. Functionality of TF downregulation was investigated by a whole blood clotting test and a flow chamber assay. TF siRNA was expressed in all twelve liveborn piglets. TF mRNA expression was reduced by 94.1 ± 4.7% in TF knockdown (TFkd) fibroblasts compared to wild‐type (WT). TF protein expression in PAEC stimulated with 50 ng/mL TNF‐α was significantly lower in TFkd pigs (mean fluorescence intensity TFkd: 7136 ± 136 vs. WT: 13 038 ± 1672). TF downregulation significantly increased clotting time (TFkd: 73.3 ± 8.8 min, WT: 45.8 ± 7.7 min, p < 0.0001) and significantly decreased thrombus formation compared to WT (mean thrombus coverage per viewing field in %; WT: 23.5 ± 13.0, TFkd: 2.6 ± 3.7, p < 0.0001). Our data show that a functional knockdown of TF is compatible with normal development and survival of pigs. TF knockdown could be a valuable component in the generation of multi‐transgenic pigs for xenotransplantation. Abstract : Pigs with siRNA mediated knockdown of tissue factor show improved characteristics of blood coagulation and are thus useful for xenotransplantation.